EMPIRICAL RESEARCH ON EXPLORING THE IMPACT AND EFFECTIVENESS OF INSTAGRAM DRIVEN CONTENT MARKETING STRATEGIES IN RAJASTHAN'S HEALTHCARE INDUSTRY - Mathur, Pallavi; Mukherjee, Tanushri; Bhagat, Neha; Singh, Rohan Shivendra; Keskar, Dr Yogesh; Singh, Nisha (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The present fast-paced digital transformation has significantly impacted on marketing strategies, amongst all sectors, including the healthcare industry. The Instagram platform, with its unique features such as visual appeal, engagement capabilities, and large user base, has developed as a significant and effective medium for content marketing among all other social media platforms. The research aims to examine the impact and effectiveness of Instagram-based content marketing strategies in the healthcare industry of Rajasthan. The primary focus of the Research is on studying the impact of this digital strategy on patient engagement, brand perception, and healthcare decision-making. The research centered on studying the responses of 200 participants, which included patients, healthcare practitioners, and social media users of Rajasthan. The study examines the influence of various types of Instagram content, including live sessions, expert Q&A, patient testimonials, and educational posts, on public understanding and trust about the various aspects of healthcare services. The findings exhibit that rigorously developed and engaging Instagram marketing strategies increase patient trust, healthcare accessibility, and reinforce industry image, thus strengthening enhanced engagement and informed healthcare decisions. The study offers valuable insights in the field of digital healthcare marketing by giving empirical insights into the effectiveness of social media, especially Instagram based content marketing strategies in the direction of imparting patient-oriented communication.